2022
DOI: 10.3389/fimmu.2022.1028102
|View full text |Cite
|
Sign up to set email alerts
|

Prospective longitudinal analysis of antibody response after standard and booster doses of SARS-COV2 vaccination in patients with early breast cancer

Abstract: IntroductionSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants brought waves of pandemics with breakthrough infections in vaccinated individuals. We analyzed the antibody responses after primary and booster vaccination in healthy controls (HC) and patients with early breast cancer (BC).MethodsIn this prospective longitudinal cohort study, the binding activity of serum antibody level against spike proteins and antigens of SARS-CoV-2 variants was measured within 21 days after each vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In our review six studies had investigated the safety and efficacy of SARS-CoV-2 booster among an extended spectrum of immunocompromised patients ( Kontopoulou et al, 2022 , Shapiro Ben David et al, 2022 , Lin et al, 2022 , Yang et al, 2022 , Shen et al, 2022 , Tenforde et al, 2022 ) while in the remaining 52 studies, researchers had studied on specific immunocompromised subgroups as follows; transplant-recipients (n = 21) ( Balsby et al, 2022 , Affeldt et al, 2022 , Brandstetter et al, 2022 , Hod et al, 2022 , Schrezenmeier et al, 2022 , Thotsiri et al, 2022 , Davidov et al, 2022 , Sriphoosanaphan et al, 2022 , Catry et al, 2022 , Peled et al, 2022 , Hod et al, 2023 , Peled et al, 2022 , Fendler et al, 2022 , Crane et al, 2023 , Benotmane et al, 2022 , Busà et al, 2022 , Cassaniti et al, 2022 , Costard-Jäckle et al, 2022 , Karaba et al, 2022 , Nafar et al, 2022 , Perrier et al, 2022 ), hematologic malignancies (n = 9) ( Diamantopoulos et al, 2022 , Goldwater et al, 2023 , Ollila et al, 2022 , Storti et al, 2022 , Terpos et al, 2022 , Piñana et al, 2023 , Fendler et al, 2022 , Fiorino et al, 2022 , Gavriatopoulou et al, 2022 ), solid tumors and cancers (n = 5) ( Benitez Fuentes et al, 2022 , Tanzilli et al, 2022 , Guven et al, 2023 , Kim et al, 2022 , Su et al, 2022 ), dialysis (n = 4) ( Affeldt et al, 2022 , Quiroga et al, 2022 , Shashar et al, 2022 , Verdier et al, 2022 ), HIV (n = 4) ( Fidler et al, 2023 , Gianserra et al, 2022 , Kling et al, 2023 , Lamacchia et al, 2022 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our review six studies had investigated the safety and efficacy of SARS-CoV-2 booster among an extended spectrum of immunocompromised patients ( Kontopoulou et al, 2022 , Shapiro Ben David et al, 2022 , Lin et al, 2022 , Yang et al, 2022 , Shen et al, 2022 , Tenforde et al, 2022 ) while in the remaining 52 studies, researchers had studied on specific immunocompromised subgroups as follows; transplant-recipients (n = 21) ( Balsby et al, 2022 , Affeldt et al, 2022 , Brandstetter et al, 2022 , Hod et al, 2022 , Schrezenmeier et al, 2022 , Thotsiri et al, 2022 , Davidov et al, 2022 , Sriphoosanaphan et al, 2022 , Catry et al, 2022 , Peled et al, 2022 , Hod et al, 2023 , Peled et al, 2022 , Fendler et al, 2022 , Crane et al, 2023 , Benotmane et al, 2022 , Busà et al, 2022 , Cassaniti et al, 2022 , Costard-Jäckle et al, 2022 , Karaba et al, 2022 , Nafar et al, 2022 , Perrier et al, 2022 ), hematologic malignancies (n = 9) ( Diamantopoulos et al, 2022 , Goldwater et al, 2023 , Ollila et al, 2022 , Storti et al, 2022 , Terpos et al, 2022 , Piñana et al, 2023 , Fendler et al, 2022 , Fiorino et al, 2022 , Gavriatopoulou et al, 2022 ), solid tumors and cancers (n = 5) ( Benitez Fuentes et al, 2022 , Tanzilli et al, 2022 , Guven et al, 2023 , Kim et al, 2022 , Su et al, 2022 ), dialysis (n = 4) ( Affeldt et al, 2022 , Quiroga et al, 2022 , Shashar et al, 2022 , Verdier et al, 2022 ), HIV (n = 4) ( Fidler et al, 2023 , Gianserra et al, 2022 , Kling et al, 2023 , Lamacchia et al, 2022 …”
Section: Resultsmentioning
confidence: 99%
“…Five studies investigated the efficacy of COVID-19 booster doses among patients with solid tumors ( Benitez Fuentes et al, 2022 , Tanzilli et al, 2022 , Guven et al, 2023 , Kim et al, 2022 , Su et al, 2022 ). Benitez et al observed higher antibody levels when comparing the antibody responses after the 1st to the 3rd and the 2nd to the 3rd vaccine doses ( Benitez Fuentes et al, 2022 ).…”
Section: Benefits Of a Booster Dose Of Covid-19 Vaccinementioning
confidence: 99%
See 2 more Smart Citations
“…This makes it easier for antigen-presenting cells, like dendritic cells, to take in and process these antigens, which then causes immune cells to recognize and respond to the tumor antigens. In addition, mannose modification is able to interact with specific receptors on the surface of tumor cells to promote intracellular phagocytosis and the internal presentation of nanoparticles [172][173][174][175][176][177][178][179][180]. Finally, the release of these immune stimulators and the presentation of tumor antigens will activate the body's immune system, especially promoting the activation and proliferation of antigen-specific T cells and B cells, thus strengthening the immune response to tumors [181][182][183][184].…”
Section: Stability and Biocompatibility Of Nanoparticlesmentioning
confidence: 99%